Chicken antibodies against venom proteins of Trimeresurus stejnegeri in Taiwan - Lee,Chi-Hsin (2020)
Abstract Background: The venom of bamboo vipers (Trimeresurus stejnegeri - TS), commonly found in Taiwan, contains deadly hemotoxins that cause severe envenomation. Equine-derived antivenom is a specific treatment against snakebites, but its production costs are high and there are some inevitable side effects. The aim of the present work is to help in the development of an affordable and more endurable therapeutic strategy for snakebites. Methods: T. stejnegeri venom proteins were inactivated by glutaraldehyde in order to immunize hens for polyclonal immunoglobulin (IgY) antibodies production. After IgY binding assays, two antibody libraries were constructed expressing single-chain variable fragment (scFv) antibodies joined by the short or long linker for use in phage display antibody technology. Four rounds of biopanning were carried out. The selected scFv antibodies were then further tested for their binding activities and neutralization assays to TS proteins. Results: Purified IgY from egg yolk showed the specific binding ability to TS proteins. The dimensions of these two libraries contain 2.4 × 107 and 6.8 × 107 antibody clones, respectively. An increase in the titers of eluted phage indicated anti-TS clones remarkably enriched after 2nd panning. The analysis based on the nucleotide sequences of selected scFv clones indicated that seven groups of short linkers and four groups of long linkers were identified. The recombinant scFvs showed significant reactivity to TS venom proteins and a cross-reaction to Trimeresurus mucrosquamatus venom proteins. In in vivo studies, the data demonstrated that anti-TS IgY provided 100% protective effects while combined scFvs augmented partial survival time of mice injected with a lethal amount of TS proteins. Conclusion: Chickens were excellent hosts for the production of neutralization antibodies at low cost. Phage display technology is available for generation of monoclonal antibodies against snake venom proteins. These antibodies could be applied in the development of diagnostic kits or as an alternative for snakebite envenomation treatment in the near future.